Conflict Resolution Between Neighbours In Bakti Makmur Village, Rokan Hilir, Riau: A Social Approach And Al-Qur'anic Values - Sari, Puspita; Azmi , Muhammad Ali (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Conflict between neighbours is a social challenge that often disrupts community cohesion, especially in rural areas with close social interactions. This research aims to examine the dynamics of social conflict in Bakti Makmur Village, Rokan Hilir, Riau, by exploring the causal factors, forms of social disintegration, and a Qur'anic values-based resolution approach. The qualitative case study method was used through in-depth interviews, participatory observation, and documentation with residents, community leaders, and religious leaders. The findings show that conflicts are often triggered by unfair business competition, social jealousy, and weak intervention of social institutions. Broken communication, innuendo on social media, and lack of islah facilitation exacerbate social disintegration. Although the values of ukhuwah, islah and itsar are often combined, the actualisation of these values is still low in daily practice. The Qur'an emphasises ukhuwah Islamiyah as the structural foundation of the ummah that must be realised through justice, empathy and social solidarity. This research also found that some residents still uphold the ethics of muamalah and tolerance in competition, representing the praxis of Qur'anic values in social life. However, the dominance of individualistic approaches and the weak role of social institutions hinder the transformation of values into social structures. This study recommends the integration of Qur'anic value-based conflict resolution strategies and local community approaches to build a peaceful, just society and create prosperous conditions